Decreased activity of all tryptophan biosynthetic enzymes due to zinc deficiency - M. Carsiotis; A. M. Meyers (Fungal Genetics Reports, 1965)
Decreased activity of all tryptophan biosynthetic enzymes due to zinc deficiency